Effect of Advertising and Product Innovation on the Performance of MSMEs During The Covid-19 Pandemic: E-Commerce as the Moderator - Kustiadi Basuki; Ari Soeti Yani; Cheeny Eillen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The background of this research is that some business operators have practiced or used e-commerce in their business activities, namely, in the Sunter Agung Village, North Jakarta. This research aims to identify the effect of advertising and product innovation on the performance of MSMEs during the Covid-19 pandemic with an e-commerce moderator. Advertising and Product Innovation are the independent variables and the performance of SMEs as the dependent variable in this research. In this research there is also a moderating variable, namely E-Commerce. Procedure for analyzing information using SmartPLS. The population in this research is MSMEs in the Sunter Agung Village, North Jakarta. Respondents in this study were taken using purposive sampling and produced 100 respondents. The analytical method in this study uses path analysis. The research results show that advertising has a positive and significant effect on MSME performance, product innovation has a positive and significant impact on MSME performance, E-commerce has a significant positive effect on MSME performance. Next, advertisements moderated by E-commerce have a negative and significant impact on the performance of MSMEs. Conversely, Product Innovation moderated by E-commerce has a positive and significant impact on the performance of MSMEs.